Linguistic and cultural diversity minority and minoritised languages as part of European linguistic and cultural diversity - Videsott, Paul 1971- (Policy Department for Citizens' Rights and Constitutional Affairs, 2023)
This study, commissioned by the European Parliament’s Policy Department for Citizens’ Rights and Constitutional Affairs, at the request of the PETI Committee, inquires about the connection between the "Protection of European linguistic and cultural diversity" and the "Protection and promotion of European minority and minoritised languages" in Europe. The situation of the European minority and minoritised languages can be seen as a barometer of the current state of European linguistic and cultural diversity. The available data show that more than two thirds of linguistic minorities within the European Union have significantly decreased in number in recent decades (1991-2011). At the pan- European level, too, two thirds of minorities have declined over the same period. The same must be assumed as to the use of the languages spoken by these minorities.